Blunted ACTH response to dexamethasone suppression-CRH stimulation in posttraumatic stress disorder - Ströhle, Andreas; Scheel, Michael; Modell, Sieglinde; Holsboer, Florian (Journal of psychiatric research, 2008)
Previous studies have suggested that patients with posttraumatic stress disorder (PTSD) have an enhanced negative feedback sensitivity of the hypothalamic–pituitary–adrenal (HPA) system and a blunted ACTH response to corticotropin releasing hormone (CRH). The effects of two dexamethasone dosages (0.75 and 1.5 mg) on the ACTH and cortisol concentrations after CRH stimulation (100 μg) were studied in eight patients with PTSD and matched healthy control subjects. Compared to healthy subjects, patients with PTSD have a blunted ACTH response to CRH. Cortisol concentrations were only significantly influenced by dexamethasone dosage. Our results give further evidence for a central role of the pituitary in reflecting changes of the negative feedback sensitivity of the HPA system in patients with PTSD.